Ten years of the UK's Equality Standard for Sport. Issue 2 (3rd April 2018) - Dwight, Adam; Biscomb, Kay
Abstract: In 2004, the four UK Sports Councils introduced the Equality Standard for Sport. The purpose of The Standard was an approach of policy development through consultation and partnership with National Governing Bodies and built on the lessons learnt through the Racial Equality Standard for Sport (2000). Furthermore, The Standard aimed to recognize the multiple nature of inequality, beyond racial grounds and embrace a wider set of protected characteristics. Whilst this widening scope to The Standard is a positive move, its methodology and focus is still largely founded on an outcome based approach grounded in an audit culture. Previous research on The Standard was critical of this over reliance on the formalized audit approach, its failure to encourage organizations to be reflective on their history and culture and to promote organizational involvement in creating equality policies. This paper provides a comparative analysis to the previous review of The Standard and aims to examine what difference it is making in terms of equality, diversity and inclusion within sports organizations. Results indicate that there is proactive work carried out by sports organizations to widen the appeal of their sports with previously underrepresented groups but it is not clear how much of this work is from a direct result of The Standard. Furthermore, although many organizations had an aspiration to achieve Intermediate Level, very few have progressed beyond the Preliminary Level.